Io ti salverò. Donne come pazienti, donne che curano - Homberg, Annelore (Il sogno della farfalla, 2006)
The article examines some aspects of the history of dynamic psychiatry where, historically speaking, research into the unconscious has always been carried out by a male doctor and a female patient. Keeping in mind that psychotherapy at the Collective Analysis involves three cardinal points; setting, transference and interpretation, we are able to reconstruct the relationship between F. A. Mesmer and his young female patients. Throughout the eighteenth century the potential and intuitions present in Mesmer’s work experienced ups and downs to end up being almost entirely forgotten. From a general incapacity on the part of doctors to interpret words that arise during therapy we reach the second half of the century characterized by a shift towards an authoritarian and positivist approach. Finally, with the advent of Freud’s work we witness the end of a dialectic and century-old research that reappears only at the end of the 50s in the 20th century.